The little book that still beats the market - Greenblatt, Joel. (Hoboken, N.J. : Wiley, 2010)
A hedge fund manager and Columbia Business School professor shows how "beating the market" can be made simple and easy for investors of any age, updated by an afterword covering the recent financial crisis.
"Updated"--Spine.
Originally published: The little book that beats the market. Hoboken, N.J. : Wiley, c2006. With new introd. and afterword.
rua 25/04/13
Loans
Keywords: Speculation; Stock exchanges